Play and the Hospitalized Child - Weininger, Otto (Canadian Journal of Counselling and Psychotherapy, 2012)
Play is the way that children are able to come to terms with reality. Throughplay children are not only able to revise their ideas and actions, but are also able toformulate ways in which they can put these ideas into use. Children who are separated from parents by reason of hospitalization experience severe anxiety and have very limited ways of coping with this painful experience. Play offers a medium through which the child may be able to express and then cope with some of these feelings. Play offers, as well, a window to the examiner, to observe the fright andpain and then, hopefully, provide some relief.